Simplified Model Predictive Current Control for Surface- Mounted Permanent-Magnet Synchronous Motor Drives with Adaptive Duty Modulation - Almazan Agustin, Crestian (International Journal of Integrated Engineering, 2023)
Parameter control and cost minimization are among the significant aspects of model predictive current controllers. However, with the conventional control scheme of fixed switching vector actuation, susceptibility to uncontrolled current ripples remains a primary concern. This paper presents a simplified approach of model predictive current controller baed on adaptive duty modulation for the surface-mounted permanent-magnet synchronous motor (SPMSM). In this method, the implementation of two successive synthesized voltage vectors adopts the adpative soft-switching combination in each control period. Experimental results validate performance improvement and optimize current predictive accuracy.